Harmony of International Education: Transformation of Innovative Community Service Program in Thailand with Al-Hidayah Foundation - Zailani, Zailani; Al Muflih, Ali Baroroh; Fuad, Ai Fatimah Nur; Sidae, Waeyosof (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
This research was motivated by collaboration between the UMSU Islamic Faculty and the Al-Hidayah Foundation in implementing the Community Service Program (KKN) in Thailand. The aim is to reveal the contribution of the Al-Hidayah Foundation in improving the quality of Islamic Religious Faculty graduates through the KKN program. This research uses a qualitative descriptive approach with data instruments in the form of observation, interviews and documentation. Data were analyzed using the Miles and Huberman model and tested via triangulation. The research results show the significant contribution of the Al-Hidayah Foundation in improving the quality of education and empowering students. Through KKN, students experience an increase in the quality of learning, application of theory in practice, and development of leadership skills and social responsibility. This collaboration also strengthens international relations between the Al-Hidayah Foundation and UMSU, opening up opportunities for cultural exchange and educational project collaboration. It is hoped that this collaboration will provide benefits to other faculties at UMSU, broaden horizons, improve the quality of education, and empower students to improve the quality of graduates.